Pelatihan Penerapan Transformasi Digital Pada Usaha UMKM Briket Tempurung AL2 Bengkulu - Astuty, Kamelia; Sudarsono, Aji; Tambunan, Dennis Rydarto; Agung, Kiemas Tando (Universitas Dehasen Bengkulu, 2022)
The application of Digital Transformation is a technological advancement that is increasingly dynamic and is expected to be well utilized by conventional business people. MSMEs as a sector that has been proven and can survive in a crisis, therefore MSMEs are encouraged to accelerate the digital transformation process that is right for every MSME business. There are several factors that cause this MSME business to not develop, one of which tends to only follow the steps of other transformation factors so as not to create the uniqueness of the MSME which will result in the loss of opportunities to have a competitive advantage over competitors. The AL2 Briquette Business is one of the SME's of Grilled Shell Briquettes with Bengkulu Province Production. But have not implemented the Digital Transformation properly. Therefore, our team of lecturers and students of the Unived Faculty of Economics provides training on the application of simple digital transformation, especially to get excellent digital skills in order to get partners for the AL2 Briquette MSME Business. The method used is delivery in the form of counseling, practice, discussion and assistance in implementing digital transformation. The results of this service are very helpful for the owner of the AL2 Briquette Business, which is expected to be able to contribute to academic understanding of technological science, especially in digital transformation related to developing old information systems to new information systems.